Farmer advisory systems and pesticide use in legume-based systems in West Africa - Tabe-Ojong, Martin Paul; Nyam, Yong Sebastien; Lokossou, Jourdain C.; Gebrekidan, Bisrat Haile (Elsevier, 2023)
Despite the adverse effects of pesticides on the environment and human health, they are a key ingredient in boosting agricultural productivity as a way of meeting global food demand. While global levels of pesticides are towering in high-income countries, pesticide use in many parts of Africa remains low, with significant impacts on agricultural productivity and food production. We use a rich longitudinal dataset to examine the relationship between farmer advisory systems and pesticide use in legume-based production systems in Ghana, Mali, and Nigeria. We find that farmers who are advised by private extension systems are approximately 8 % more likely to use pesticides at an extensive level. They also use pesticides more intensively (41 %). On the other hand, farmers advised by public extension systems are about 5 % more likely to extensively use pesticides. These farmers are observed to reduce the intensive use of pesticides by about 14 %. Furthermore, we also show that farmers advised by joint private-public extension systems are about 4 % more likely to use pesticides as well as reduce their intensity of use by approximately 11 %. At the various country levels, there exists significant heterogeneity in the relationship between advisory systems and pesticide use, suggesting that context matters. Of course, the pesticide regulatory systems and the institutional environments in these countries vary greatly. Given these findings, our study offers key entry and leveraging points for increasing pesticide use at levels that limit their environmental and human effects but may ascertain increased agricultural productivity and food production.